Small towns face big challenge: The management of piped systems after the water sector reform in Ghana - Irit Eguavoen; Eva Youkhana (University of Bonn, Center for Development Research (ZEF), 2008)
As the outcome of drinking water sector reforms in Ghana, three different management options are realized for small town water systems. Many piped systems remain centrally managed by the Ghana Water Company Limited even though a policy of community-based management is favoured. Alternatively, a management option of public private partnerships is fostered. The paper reviews and compares two of the realized options: public-private partnerships and community-based management. It asks what the outcomes of these two options are for the sustainability of small town water supply as well as whether one of the two options is preferable and should be pushed by policy. Further, the paper aims at showing some of the limits of participatory approaches in water development practice. It concludes that none of the management options offers a solution to the prevalent problem of failing water systems but both carry the potential to do so, if a system of continuous support and supervision for the managing communities would be established. Such tandem option between water administration and communities is still at its pilot stage.
urn:nbn:de:0202-20080911267
Keywords: 330; Water; community-based management; PPP; Ghana